Valorization of fast-growing Paulownia wood to green chemicals and green hydrogen - Lee, Li Quan (2024)
Fast-growing plants with a high carbon fixation capability are promising candidates for mitigating climate change and serving as a renewable resource to replace fossil fuels. Nonetheless, their short lifespan and extensive use lead to the significant accumulation of underutilized waste. While conventional thermal energy extraction remains dominant in biomass utilization, the lack of appropriate carbon capture and storage techniques results in unavoidable CO2 emissions. In contrast, the fine reforming of lignocellulosic biomass offers the potential to reduce CO2 emissions. However, the polymeric, complex and rigid structure of lignocellulosic biomass poses challenges, necessitating energy-intensive pretreatment, where the balance between wood particle size reduction (and thus energy consumption) and pretreatment duration is often overlooked. Herein, we developed a facile energy-saving microwave-hydrothermal method to advance the utilization of fast-growing Paulownia. The optimized sugars (xylose and glucose) after pretreatment can be further converted to formate via a hybrid electrolysis process with the cogeneration of green hydrogen. Both xylose and glucose can be readily converted to formate with high yield and selectivity. This process can be directly powered by PV panel without the safety concerns of hydrogen crossover because oxygen evolution is greatly suppressed. This solar-driven hybrid electrolysis of pretreated Paulownia suggests a pathway to cogenerate green chemicals and green fuels from fast-growing woods while also storing energy from renewable sources in chemical bonds. Overall, this novel synthesis process for green chemicals contributes to the decarbonization efforts and sustainable development initiatives.